Evaluasi User Experience Sistem Informasi Akademik Universitas Wiraraja Menggunakan Metode UEQ - Silvana, Fanni; Suryanto, Tri Lathif Mardi (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2024)
Information technology is a vital component in an educational institution. The Academic Information System (SIAKAD) owned by Wiraraja University is a system designed to manage academic data and provide academic-related information to students. The SIAKAD of Wiraraja University has never undergone evaluation, and user-perceived constraints have been identified. Therefore, this research conducts a user experience evaluation of SIAKAD. The evaluation employs the User Experience Questionnaire (UEQ) method. The population size for this study is 248 data points. The User Experience Questionnaire (UEQ) evaluation yields positive ratings. Attractiveness has an average score of 1.45, clarity scores 1.64, efficiency scores 1.12, dependability scores 1.16, stimulation scores 1.05, and novelty scores 0.43. However, the Novelty scale is the one with the lowest mean value in the benchmark results, which is 0.43. This suggests that SIAKAD lacks innovation, exhibits limited creativity, and indicates that SIAKAD users do not perceive any unique differences compared to other Academic Information Systems applications. Therefore, this scale should be the focus of improvement among the other scales.Keywords: User experience; User Experience Questionnaire; Academic Information Systems; BenchmarksÂ AbstrakTeknologi informasi merupakan komponen penting dalam sebuah institusi Pendidikan. Sistem Informasi Akademik (SIAKAD) milik Universitas Wiraraja merupakan sistem yang dirancang untuk mengelola data akademik dan memberikan informasi terkait akademik mahasiswa. SIAKAD Universitas Wiraraja belum pernah dilakukan evaluasi, dan ditemukan kendala yang dirasakan pengguna. Maka dalam penelitian ini dilakukan evaluasi pengalaman pengguna SIAKAD. Evaluasi menggunakan metode User Experience Questionnaire (UEQ). Jumlah populasi pada penelitian ini didapat 248 data. Evaluasi User Experience Questionnaire (UEQ) memiliki penilaian yang baik. Daya tarik memiliki nilai rata-rata 1.45, kejelasan memiliki nilai 1.64, efisiensi bernilai 1.12, ketetapan b bernilai 1.16, stimulasi bernilai 1.05, dan kebaruan bernilai 0.43. Namun skala Kebaruan merupakan skala dengan nilai mean terendah pada hasil benchmark yakni 0.43 yang menggambarkan SIAKAD kurang memiliki inovasi, kreativitas yang terbatas, dan menunjukkan pengguna SIAKAD tidak merasakan perbedaan yang unik dengan aplikasi Sistem Informasi Akademik lainnya. Sehingga skala tersebut dapat menjadi fokus peningkatan diantara skala lainnya.Â